Myoanatomy and anterior muscle regeneration of the fireworm Eurythoe cf. complanata (Annelida: Amphinomidae). (23rd November 2015) - Weidhase, Michael; Bleidorn, Christoph; Beckers, Patrick; Helm, Conrad
ABSTRACT: Amphinomidae or so‐called "fireworms" are known for their inflammatory substances and their regeneration ability. Recent transcriptome‐based molecular analyses revealed that these remarkable annelids are a basal branching taxon outside the annelid main radiation (Pleistoannelida). Although several studies dealing with analyses of the morphology of these annelids have been published, detailed investigations of the anterior muscle regeneration and the musculature in general are largely lacking for amphinomids. Using histology, phalloidin labeling together with subsequent confocal laser scanning microscopy (cLSM), and further light microscopic image acquisition of different regeneration stages, we here present the first morphological study describing the myoanatomy and muscular regeneration. During anterior muscular regeneration, longitudinal muscle bundles develop prior to transverse muscle fibers and segment boundaries. Additionally, Eurythoe cf. complanata develops an independent muscular ring surrounding the mouth opening in an early stage of regeneration. Detailed investigation of adult body wall musculature and the parapodial muscle complex in amphinomids show that E . cf. complanata bears well‐developed dorsal and ventral longitudinal muscle bundles as well as outer transverse muscles comparable to the pattern described for several Pleistoannelida. Furthermore, the biramous parapodia possess a complex meshwork of distinct muscle fibers allowing detailed comparisons with other annelid families. J. Morphol. 277:306–315, 2016. © 2015 Wiley Periodicals, Inc.